Mountain building processes in the northern Norwegian Caledonides - Examining Caledonian continental collision using a combination of structural mapping, phase equilibrium modelling and geochronology - Faber, Carly (UiT Norges arktiske universitet, 2018)
Studying orogenesis allows us to better understand the construction of continental crust and the lower crustal processes that occur in modern orogenic belts (e.g. the Himalaya). The Scandinavian Caledonides formed when Laurentia and Baltica collided during the Silurian/Devonian, and allow for direct study of mid- to lower crustal metamorphism in a continental collision zone. This work focuses on the allochthonous Kalak (KNC) and Reisa (RNC) nappe complexes in northern Norway. The KNC is comprised of several nappes that underwent pre-Caledonian Neoproterozoic evolutions, and its paleogeographic origin has been strongly debated in recent years. This work aims to better constrain the timing, conditions and tectonic context of pre-Caledonian and Caledonian metamorphism in the KNC and RNC by combining structural mapping, phase equilibrium modelling, and geochronology. Papers I and III examine the timing and conditions of metamorphism within the different units of the KNC, and Paper II describes tectonic events in the Reisa Nappe Complex (RNC) and discusses a possible Caledonian tectonic evolution for northern Norway. In paper I we show that the KNC correlates with the Sørøy terrane, defined as part of the upper KNC in Finnmark. In Paper III we describe upper and lower KNC nappes in the field area that show different pre-Caledonian evolutions, and that Caledonian metamorphism may have followed an anticlockwise P-T path. In paper II we describe an anticlockwise P-T path for Caledonian metamorphism that occurred over ~10 Ma. Early Silurian heating, partial melting, and intrusion of tholeiitic gabbro (probably in a compressional setting) was followed by higher pressure, lower temperature shearing associated with nappe stacking during crustal thickening. The anticlockwise P-T path for Caledonian metamorphism in northern Norway records either the subduction of a back-arc, or slab break-off at the onset of subduction of Baltica continental crust before ~440 Ma.